Expression of a set of glial cell-specific markers in the Drosophila embryonic central nervous system. - Ahn, H.J.; Jeon, S.H.; Kim, S.H. (BMB Reports, 2014)
The types of glia in the central nervous system (CNS) of the Drosophila embryo include longitudinal glia (LG), cell body glia (CBG), and peripheral glia (PG). Transcription factors, such as glial cell missing and reverse polarity, are well-established general glial cell markers. Only a few glial cell-specific markers have been identified in the Drosophila embryonic CNS, thus far. In the present study, we employed the glial cell-specific markers for LG (vir-1/CG5453 and CG31235), CBG (fabp/CG6783 and CG11902), and PG (CG2310 and moody/CG4322), and comprehensively analyzed their expression patterns, during the embryonic CNS development. Our study validated the specificity of a set of glial markers, and further revealed their spatio-temporal expression patterns, which will aid in the understanding of the developmental lineage, and investigating their role in the development and homeostasis of the Drosophila CNS in vivo. [BMB Reports 2014; 47(6): 354-359].